2018
DOI: 10.1121/1.5063821
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the primary tone phase variation method: An exclusive way of isolating the frequency-following response components

Abstract: The primary tone phase variation (PTPV) technique combines selective sub-averaging with systematic variation of the phases of multitone stimuli. Each response component having a known phase relationship with the stimulus components phases can be isolated in the time domain. The method was generalized to the frequency-following response (FFR) evoked by a two-tone (f 1 and f 2) stimulus comprising both linear and non-linear, as well as transient components. The generalized PTPV technique isolated each spectral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…As eight different SCs were expected to be potentially present in the two-tone evoked FFR response ( Lucchetti et al, 2018 ), implementation of the gPTPV method required that each of the five EFR stimuli be composed of a subset of eight different sub-stimuli s k (t) differing only by their primary phases φ 1 and φ 2 . Values for φ 1 and φ 2 for the k = { 1 , ..., 8 } sub-stimuli are found on Table 2 Table 2 Two-tone stimulus primary phase values φ 1 and φ 2 for the set of 8 stimuli indexed by k.…”
Section: Efr Time-domain Isolationmentioning
confidence: 99%
See 3 more Smart Citations
“…As eight different SCs were expected to be potentially present in the two-tone evoked FFR response ( Lucchetti et al, 2018 ), implementation of the gPTPV method required that each of the five EFR stimuli be composed of a subset of eight different sub-stimuli s k (t) differing only by their primary phases φ 1 and φ 2 . Values for φ 1 and φ 2 for the k = { 1 , ..., 8 } sub-stimuli are found on Table 2 Table 2 Two-tone stimulus primary phase values φ 1 and φ 2 for the set of 8 stimuli indexed by k.…”
Section: Efr Time-domain Isolationmentioning
confidence: 99%
“…Furthermore, it has been suggested that there may be cortical sources contributing to the FFR at frequencies below 200 Hz ( Coffey et al, 2019;Tichko and Skoe, 2017 ). Moreover, along the auditory neuraxis, more centrally located generators are more affected by sleep and sedation ( Aoyagi et al, 1993;Lucchetti et al, 2018 ). Results are therefore likely to differ according to the combination of stimulus spectra, recording montages and sleep-wake state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy at 2F 0 in S(f ) may reflect one or more of the following sources: (1) rectifier distortion to carrier energy at F 0 , (2) beating between (carrier) harmonics that are separated by 2F 0 , and (3) effects of transduction nonlinearities on the beating between (carrier) harmonics that are separated by F 0 . In these special cases, additional stimulus phase variations can be used to separate out these components (Billings and Zhang, 1994;Lucchetti et al, 2018).…”
Section: Alternating-polarity Stimulimentioning
confidence: 99%